2021
DOI: 10.14254/jems.2021.6-1.3
|View full text |Cite
|
Sign up to set email alerts
|

The status of immigrants on Italian labour market in the context of economic decline: Evidence from survey, macroeconomic and big data

Abstract: Considering the impact of economic crisis on Italian labour market, the aim of this paper is to analyse the status of immigrants from Italy in the labour field using more sources of data: survey data from the research “Case study of Labour Force Survey”, macroeconomic data from official statistics of Eurostat and big data associated to Internet queries on Google. Survey analysis for the 20 regions in Italy confirmed the foreign women advantage of finding a job better than foreign men. The decline in the GDP at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Choi et al (2020) presented the psychological resilience and coping mechanisms of immigrants and emphasized the importance of developing policies that aim to strengthen the mental health of immigrants. Simionescu (2021) used microeconomic and macroeconomic big data and revealed the possibilities of immigrants to be employed with high wages. Ahmed et al (2020) shared the geographical structure of immigrant camp sites and drew attention to the risks in these areas and improvements that should be made.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Choi et al (2020) presented the psychological resilience and coping mechanisms of immigrants and emphasized the importance of developing policies that aim to strengthen the mental health of immigrants. Simionescu (2021) used microeconomic and macroeconomic big data and revealed the possibilities of immigrants to be employed with high wages. Ahmed et al (2020) shared the geographical structure of immigrant camp sites and drew attention to the risks in these areas and improvements that should be made.…”
Section: Discussionmentioning
confidence: 99%
“…Wilson et al (2020) reported that these groups had lower health expenditures compared to individuals born in the US where they immigrated, it was estimated that approximately half of unregistered immigrants worked without insurance, and it was determined that this rate was significantly higher compared to the rates of registered immigrants and individuals born in the US (Wilson et al, 2020). Using regression models, Simionescu (2021) determined that immigrants with education degrees higher than high school had lower chances of being employed compared to those with education degrees of high school or below, and those who came from households with higher income preferred to wait until they found a betterpaying job. Ruhnke et al (2012) showed that using machine learning, especially the Random Forest Algorithm, to determine the legal status of refugees provided more accurate results in identifying undocumented refugees and minimized prejudice.…”
Section: Biopsychosocial Health and Socioeconomic Statusmentioning
confidence: 99%